A 472-SNP panel for pairwise kinship testing of second-degree relatives. (May 2018) - Mo, Shao-Kang; Ren, Zi-Lin; Yang, Ya-Ran; Liu, Ya-Cheng; Zhang, Jing-Jing; Wu, Hui-Juan; Li, Zhen; Bo, Xiao-Chen; Wang, Sheng-Qi; Yan, Jiang-Wei; Ni, Ming
Highlights: A new 472-SNP panel for kinship analysis is proposed and validated by MPS. SNP2kin could distinguish 2nd-degree relatives from the unrelated. The testing power of ∼6.45 SNPs are equivalent to one STR for 2nd-degree relatives. Ab stract: Kinship testing based on genetic markers, as forensic short tandem repeats (STRs) and single nucleotide polymorphisms (SNPs), has valuable practical applications. Paternity and first-degree relationship can be accurately identified by current commonly-used forensic STRs and reported SNP markers. However, second-degree and more distant relationships remain challenging. Although ∼10 5 –10 6 SNPs can be used to estimate relatedness of higher degrees, genome-wide genotyping and analysis may be impractical for forensic use. With rapid growth of human genome data sets, it is worthwhile to explore additional markers, especially SNPs, for kinship analysis. Here, we reported an autosomal SNP panel consisted of 342 SNP selected from >84 million SNPs and 131 SNPs from previous systems. We genotyped these SNPs in 136 Chinese individuals by multiplex amplicon Massively Parallel Sequencing, and performed pairwise gender-independent kinship testing. The specificity and sensitivity of these SNPs to distinguish second-degree relatives and the unrelated was 99.9% and 100%, respectively, compared with 53.7% and 99.9% of 19 commonly-used forensic STRs. Moreover, the specificity increased to 100% by the combined use of these STRs and SNPs. The 472-SNP panel could also greatly facilitate the discrimination among different relationships. We estimated that the power of ∼6.45 SNPs were equivalent to one forensic STR in the scenario of 2nd-degree relative pedigree. Altogether, we proposed a panel of 472 SNP markers for kinship analysis, which could be important supplementary of current forensic STRs to solve the problem of second-degree relative testing.